Compound-choking theory for supersonic ejectors working with real gas. (15th July 2021) - Croquer, Sergio; Fang, Yu; Metsue, Antoine; Bartosiewicz, Yann; Poncet, Sébastien
Abstract: The performance of supersonic ejectors is mainly limited by the choking of the flow. Below a critical pressure, the entrainment capability of the ejector remains indeed constant. As the coefficient of performance of ejector-based heat driven refrigeration cycles (HDRC) is directly linked to the ejector entrainment ratio, it constitutes a real limitation towards better overall cycle performance. The compound-choking criterion has recently demonstrated to better explain this limitation compared to the Fabri-choking theory for supersonic ejectors working with air. However, as all ejector-driven HDRCs work with real gas refrigerants, this criterion needs to be extended to real gases. In the present work, the compound-choking criterion is first extended analytically to real gases. Wall-resolved turbulence modelings for supersonic ejectors working with R134a and blends of R134a and HydroFluoroOlefeins (HFO) are then performed. An improved thermodynamic model is finally used to demonstrate the superiority of the compound-choking criterion over the Fabri-choking one for supersonic ejectors. Results show that the β parameter constitutes an unambiguous indicator of the ejector choking condition, much better suited to determine the operating regime than the sonic line criterion. Moreover, the mean error in entrainment ratio predictions is reduced from 17.54 % to 5.28 % when using the compound-choking theory instead of the Fabri-choking one, with virtually no difference in the complexity or computational cost of the model. Highlights: The compound-choking theory is applied to single-phase supersonic ejectors. The compound-choke theory leads to more accurate supersonic ejector models. The condition β < 0 is a clear indicator of the supersonic ejector operating regime. The theory is applicable to different operating conditions and working fluids.